HIV-1 Subtype distribution in morocco based on national sentinel surveillance data 2004-2005. - Akrim, M; Lemrabet, S; Elharti, E; Gray, R; Tardy, J; Cook, R; Salemi, M; Andre, P; Azarian, T; Aouad, R (BioMed Central, 2012)
BACKGROUND: Little is known about HIV-1 subtype distribution in Morocco. Some data suggest an emergence of new HIV subtypes. We conducted phylogenetic analysis on a nationally representative sample of 60 HIV-1 viral specimens collected during 2004-2005 through the Morocco national HIV sentinel surveillance survey. RESULTS: While subtype B is still the most prevalent, 23.3% of samples represented non-B subtypes, the majority of which were classified as CRF02_AG (15%). Molecular clock analysis confirmed that the initial introduction of HIV-1B in Morocco probably came from Europe in the early 1980s. In contrast, the CRF02_AG strain appeared to be introduced from sub-Saharan Africa in two separate events in the 1990s. CONCLUSIONS: Subtype CRF02_AG has been emerging in Morocco since the 1990s. More information about the factors introducing HIV subtype-specific transmission will inform the prevention strategy in the region.